Integrating ethnomathematics into mathematical modeling: Development of student worksheets based on the Bidar Boat festival - Wijaya, Aldi Putra; Darmawijoyo, Darmawijoyo; Somakim, Somakim; Julaiha, Ellah (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aimed to develop and evaluate culturally contextualized student worksheets that integrate mathematical modeling with ethnomathematical elements from the Bidar Boat Festival. The goal was to enhance students’ modeling competencies and engagement. Method: The research employed a design-based research (DBR) approach, consisting of a preliminary study and a formative evaluation phase through iterative prototyping. Data collection involved expert validation, classroom observations, student interviews, and written assessments across three cycles with 24 junior high school students. Findings: The developed worksheets were found to be highly valid and practical. Students demonstrated strong performance on key modeling competencies: 97.5% understood the tasks, 93.54% translated real-life contexts into mathematical models, 81.88% applied mathematical operations accurately, and 80.42% interpreted results appropriately. Additionally, the learning tools enhanced student motivation, cultural awareness, and mathematical understanding. Significance: Embedding local cultural contexts, such as the Bidar Boat Festival, into mathematics instruction can bridge abstract mathematical concepts with students' lived experiences. The approach not only improved cognitive learning outcomes but also encouraged reflective thinking and cultural appreciation. The study contributes a replicable model for implementing culturally responsive, competency-based mathematics education.